2020
DOI: 10.37716/hbab.2020010201
|View full text |Cite
|
Sign up to set email alerts
|

An fNIRS examination of the neural correlates of mental rotation in preschoolers

Abstract: This study examined the neural correlates of mental rota on (MR) in preschoolers using func onal near-infrared spectroscopy (fNIRS). Fortyeight preschoolers completed a MR task in which they were asked to rotate a test s mulus to match a target s mulus. Results of compara ve and General Linear Model (GLM) analyses revealed significant differences between the High Performance (HP) and Low Performance (LP) groups. The two groups differed significantly in oxyhaemoglobin (HbO) change in Brodmann Areas (BAs) 6, 9 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…The regions of interest (ROIs) were located at Brodmann Areas (BAs) 6, 8, 9, 10, 40, and 44 (see Figure 4 ). Previous studies have shown that these areas might be activated during cognitive shifting, mental rotation, and other preschoolers’ cognitive activities ( Moriguchi and Hiraki, 2009 ; Wu et al, 2020 ). Ten channels were located in the right frontal cortex, and seven channels were located in the prefrontal cortex (see Figure 4 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The regions of interest (ROIs) were located at Brodmann Areas (BAs) 6, 8, 9, 10, 40, and 44 (see Figure 4 ). Previous studies have shown that these areas might be activated during cognitive shifting, mental rotation, and other preschoolers’ cognitive activities ( Moriguchi and Hiraki, 2009 ; Wu et al, 2020 ). Ten channels were located in the right frontal cortex, and seven channels were located in the prefrontal cortex (see Figure 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…All these studies, however, were conducted with adult participants. Recently, Wu et al (2020) examined the neural correlates of MR in preschoolers using functional near-infrared spectroscopy (fNIRS) and found that BA6, BA9, BA44 were involved in the MR processing. But the role of working memory in preschoolers’ MR has not been explored, even though it is substantially engaged in mental rotation ( Gauthier et al, 2002 ; Hyun and Luck, 2007 ).…”
Section: Indroductionmentioning
confidence: 99%
See 3 more Smart Citations